Fetal mesenchymal hamartoma of the liver: A case report and literature review - Liu, Xin; Tian, Sha; Zhu, Zhenchuang; Peng, Fei; Yuan, Qiang; Duan, Xufei; Yan, Xueqiang (Frontiers in Pediatrics, 2022)
This paper reports the diagnosis and treatment process of a case of fetal mesenchymal hamartoma of the liver(MHL), and reviews the previous literature reports.At 38+2 weeks of gestation, prenatal ultrasound found a well-bounded mixd mass ,which was located at the lower edge of the right lobe of the liver and in front of the right kidney of the fetus, but the source and nature of the mass were not clear by ultrasound.Due to the approaching due date, the fetus showed no other abnormal symptoms, and no special treatment was given with the consent of the family members. A female fetus was delivered weighing 3520 g at 39 weeks.An exploratory laparotomy was performed on the eighth day after delivery.During the operation, it was found that the tumor originated from the fifth,sixth and seventh hepatic segment and the corresponding hepatic segment were removed.The infant recovered uneventful and was discharged on the 6th day after surgery. Follow-up at 2 years showed a thriving young girl,and there was no tumor recurrence.